Labor Market Adjustment to Third Party Competition: Evidence from Mexico - Raymond Robertson; Timothy J. Halliday; Sindhu Vasireddy (Institute of Labor Economics (IZA), 2018)
China's exports reduce wages in importing countries, but few studies have looked at competition in third party markets. We examine labor market outcomes in Mexico's apparel and textile sectors associated with U.S. apparel and textile imports from China. Using data on U.S. imports in conjunction with quarterly Mexican labor force surveys, we show that U.S. imports from China are associated with a reduction of employment in Mexico's textile and apparel sectors. These effects are the most pronounced for the least educated. Wages were not impacted on net except for the poorest indicating stronger local labor market ties in the left tail of the wage distribution. Notably, reductions in labor demand due to reduced textile imports had spill-overs beyond these sectors. Finally, the effects of trade-induced demand shocks dissipate after about two quarters indicating low firm-level adjustment costs.
Keywords: F16; J31; 330; apparel; China; Mexico; trade; wages; inequality